Network mapping among the functional domains of Chikungunya virus nonstructural proteins. Issue 10 (30th May 2014) - Rana, Jyoti; Rajasekharan, Sreejith; Gulati, Sahil; Dudha, Namrata; Gupta, Amita; Chaudhary, Vijay Kumar; Gupta, Sanjay
ABSTRACT Formation of virus specific replicase complex is among the most important steps that determines the fate of viral transcription and replication during Chikungunya virus (CHIKV) infection. In the present study, the authors have computationally generated a 3D structure of CHIKV late replicase complex on the basis of the interactions identified among the domains of CHIKV nonstructural proteins (nsPs) which make up the late replicase complex. The interactions among the domains of CHIKV nsPs were identified using systems such as pull down, protein interaction ELISA, and yeast two‐hybrid. The structures of nsPs were generated using I‐TASSER and the biological assembly of the replicase complex was determined using ZRANK and RDOCK. A total of 36 interactions among the domains and full length proteins were tested and 12 novel interactions have been identified. These interactions included the homodimerization of nsP1 and nsP4 through their respective C‐ter domains; the associations of nsP2 helicase domain and C‐ter domain of nsP4 with methyltransferase and membrane binding domains of nsP1; the interaction of nsP2 protease domain with C‐ter domain of nsP4; and the interaction of nsP3 macro and alphavirus unique domains with the C‐ter domain of nsP1. The novel interactions identified in the current study form a network of organized associations that suggest the spatial arrangement of nsPs in the late replicase complex of CHIKV. Proteins 2014; 82:2403–2411. © 2014 Wiley Periodicals, Inc.